RAKE MANAGEMENT SYSTEM (RMS): OPERATIONAL ASPECT OF FREIGHT OPERATIONS INFORMATION SYSTEM (FOIS) FOR INDIAN RAILWAYS (IR) (International Journal of Engineering and Computer Science, 2017)
This paper explores need, development and main features operational subsystem of FOIS for IR which is called Rake Management system. It is a system for management and control of freight movement that also assists managers to optimize asset utilization. It has main advantage of providing real time data for wagons/ rake for proper decision making. The paper also explores advantages and certain shortcomings in the interface mechanisms and future integration with latest technologies